(untitled) - Levitzky, Michael G. (New York, 1995)
This introductory/refresher text provides a grounding in the aspects of pulmonary physiology crucial to understanding clinical medicine. Its approach stresses comprehension of applying fundamental physiologic principles to different clinical situations or different aspects of the respiratory system. Each chapter begins with a set of learning objectives, then provides explanations of physiologic mechanisms, demonstrating the role of these mechanisms in different pathologic states. In addition, study questions - with fully explained answers - are included for self-testing and review.
Keywords: Lungs,Phổi; Physiology,Sinh lý học